(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2026)
This text presents a cartography of the creative practices of digital projection projects developed with the Santa Catarina-based group Eranos Círculo de Arte, reflecting on how the medium is constituted in relation to the cast, audience, and set design in the theatrical event. Based on scenic experiences, it proposes three gradations of use: audiovisual, action-and-reaction, and spatial; articulated to the concept of apparatus. Engaging with Dubatti, Foucault, Simondon, and Winner, it discusses the ethical, political, and poetic dimensions of the technique.